MyEmergencyAssistant device: A conceptual solution in enhancing the quality of life for the disabled and elderly - Qushem, Umar; Ahmad Dahlan, Abdul Rahman; Mohd Gani, Ahmad Shahril (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Numerous studies have been conducted in the field of assistive technology for elderly and disabled. However, the overall user needs are rarely considered and understood. There is a dire need for a holistic solution to keep away dangerous happenings especially to the disabled or elderly people, who are physically fragile and feeble. This paper surveys the needs, the pains, the gains, and the challenges faced by the elderly and disabled at home, workplaces and other common vicinities. Assistive technology-based solutions for today tomorrow are to help those vulnerable people to live better and safer are researched in this study. This study proposes a conceptual MyEmergencyAssistant solution, an integrated assistive technology embedded with customized buttons as an emergency device in enhancing the quality of life and safety for the disabled and elderly community. In addition, literature-review unveils user needs based on emergency situations. This conceptual MyEmergencyAssistant solution is developed using the Environmental Map (EM), Business Model Canvas (BMC), and Value Proposition Diagram (VPD) suite of tools.